Virtual Hospitalization at Home After the Covid-19 Pandemic: Time to Consider Our Future Community Healthcare Options. (July 2022) - Boone, Emily J.; Shammash, Jonathan B.
The concept of acute hospitalization at home has been described for over 3 decades. Its scope, however, was largely limited to small experimental trials and pilot studies. The Covid-19 pandemic changed these circumstances. The convergence of the critical need for acute hospital beds along with the growing sophistication and comfort in virtual monitoring facilitated the rapid deployment of hospitalization at home throughout many communities in the United States. Now in the waning times of the pandemic, community health leaders and health systems are questioning what the future role of home virtual hospitalization might be. Might this concept be relegated to only future times of critical bed shortage, or might it be part of a true change in community healthcare delivery.